The Role of Color and Packaging Shape on Consumer Emotional Responses: A Neuromarketing Study With Eeg - Nugroho, Dony Ari (Eduvest - Journal of Universal Studies, 2025)
Packaging design, particularly color and shape, plays a crucial role in shaping consumer perceptions and emotional responses toward a product, ultimately influencing purchasing decisions. With advances in neuromarketing technology, the use of electroencephalography (EEG) enables researchers to objectively analyze how the brain responds to various visual elements in packaging, including levels of engagement and emotions evoked. This study aims to examine the impact of packaging color and shape on consumers’ emotional responses using EEG, providing insights for companies in designing more effective packaging to attract attention and enhance consumer preferences. A qualitative descriptive method was employed to understand the influence of color and shape on consumer emotions. Data were collected through documentation, including observation notes, interview transcripts, video recordings, and literature reviews related to neuromarketing and packaging design. Thematic analysis was used to identify patterns of emotional responses, offering in-depth insights into how visual packaging elements affect consumer purchasing decisions. The findings indicate that color and shape play a significant role in eliciting emotional responses that influence consumer preferences and purchasing decisions. Bright and contrasting colors tend to attract attention and evoke positive emotions, while ergonomic and unique packaging shapes enhance emotional engagement and perceived product quality. This study confirms that visual packaging elements contribute to consumers’ sensory and psychological experiences, which can be leveraged in marketing strategies to increase product appeal